Efficient CuO/ZnO/ZnAl layered double hydroxide photocatalyst for methyl orange degradation - Ibrahim, Zainab Hussaina; Zainal, Zulkarnain; Lim, Hong Ngee; Mohamad Jaafar, Adila; Wahid, Mohd Haniff (Avestia Publishing, 2025)
Dye-contaminated wastewater presents urgent environmental challenges requiring efficient treatment methods. This study reports a novel CuO/ZnO/ZnAl layered double hydroxide (LDH) photocatalyst synthesized via a one-pot modified co-precipitation and hydrothermal method optimized at 100 °C for 1 hour to preserve the LDH layered structure and enhance adsorption. Partial substitution of Zn²⁺ by 20 mol% Cu²⁺ formed CuO/ZnO heterojunctions, significantly improving light absorption by narrowing the bandgap from 3.06 to 2.46 eV and suppressing charge recombination. Under optimized conditions (0.125 g/L catalyst, 60 mg/L dye, pH 9), the catalyst achieved over 90% methyl orange degradation under both UV and visible light, with superoxide radicals as the dominant reactive species and excellent stability over three reuse cycles. These results demonstrate the synergistic effect of CuO and ZnO within the LDH matrix, providing a facile, effective approach for wastewater remediation through enhanced photocatalytic performance.